2015
DOI: 10.1007/s00267-015-0527-8
|View full text |Cite
|
Sign up to set email alerts
|

Enterprise-Level Motivations, Regulatory Pressures, and Corporate Environmental Management in Guangzhou, China

Abstract: This study examines the effects of internal motivations and external pressures on the integration of environmental management (EM) practices within manufacturing operations in China. The moderating role of perceptions toward the regulatory process is also considered along with comparisons between wholly Chinese-owned and foreign-owned enterprises. From a sample of 131 manufacturing companies in the Guangzhou area, it was found that the salience of fees and fines has a strong positive influence on perceptions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…Yet, with the present reference to just three personal attributes, Inner drive, Tolerance to stress and Enterprise, a markedly lower expression was obtained among the police leadership. The necessity for enterprise development and incorporation with leader roles is stipulated over a wide range of occupational features, including governance, environmental management, security risk management and organizational resilience [23][24][25]. The opportunities for building Inner drive within leadership are abundant: for example, it been found that autonomous motivation (intrinsic, Inner drive) and an autonomysupportive implementations of coaching models based upon selfdetermination programs [26] predicted positively the proximal transference of attribute (i.e., immediately after the training program) and perception of an autonomy-supportive climate in the sports club predicted positively the distal transference (i.e., one year after the training program).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, with the present reference to just three personal attributes, Inner drive, Tolerance to stress and Enterprise, a markedly lower expression was obtained among the police leadership. The necessity for enterprise development and incorporation with leader roles is stipulated over a wide range of occupational features, including governance, environmental management, security risk management and organizational resilience [23][24][25]. The opportunities for building Inner drive within leadership are abundant: for example, it been found that autonomous motivation (intrinsic, Inner drive) and an autonomysupportive implementations of coaching models based upon selfdetermination programs [26] predicted positively the proximal transference of attribute (i.e., immediately after the training program) and perception of an autonomy-supportive climate in the sports club predicted positively the distal transference (i.e., one year after the training program).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in order to increase profits, enterprises have to establish an environmental protection image and undertake corresponding social responsibilities of environmental protection [ 44 ]. Moreover, enterprises are also willing to develop or introduce new technology or new energy to reduce the cost of environmental pollution [ 45 ]. Table 1 summaries the group benefits in the establishment of environmental governance index system.…”
Section: Methodsmentioning
confidence: 99%
“…Viewing the network, we identified several co-occurrence disciplinary groups. The first group was composed of ‘Environmental Studies,’ ‘Economics’, ‘Business’, and ‘Management’, where researchers studied environmental regulation as a factor in economic, business, and management activities [ 39 , 40 , 41 ]. The second group consisted of ‘Environmental Sciences’, ‘Engineering, Environmental’, ‘Green and Sustainable Science and Technology’, ‘Ecology’, ‘Development Studies’, ‘Water Resources’, and ‘Plant Sciences’, where environmental regulations were considered as a controlling activity in biology and ecology process [ 42 ] or policy subject in environmental issue [ 43 ].…”
Section: Development Status Of Environmental Regulations Reflected By...mentioning
confidence: 99%